Tolerability of cabazitaxel in patients with metastatic castration-resistant prostate cancer progressing after docetaxel and abiraterone acetate: a single-institution experience. Issue 8 (September 2015) - Francini, Edoardo; Fiaschi, Anna I.; Petrioli, Roberto; Laera, Letizia; Bianco, Vincenzo; Ponchietti, Roberto; Roviello, Giandomenico
Abstract : Both abiraterone acetate (AA) and cabazitaxel (Cbz) have been shown to prolong survival in patients with metastatic castration-resistant prostate cancer (mCRPC) progressing during or after docetaxel (D). Although no standard sequencing has been established as yet, Cbz has recently been proven to be active after AA. However, to date, few data are available on its safety in this setting. Therefore, the primary endpoint of this study was to investigate Cbz tolerability in mCRPC patients treated previously with D and AA. From April 2011 to the present, 43 mCRPC patients received AA after D at our institution. Of these, 22 patients were subsequently treated with Cbz and were evaluable for toxicity in the present retrospective study. Cbz was administered at a dose of 25 mg/m 2 plus 10 mg oral prednisone every 3 weeks. Adverse events (AEs) were reported using the NCI CTCAE (National Cancer Institute Common Terminology Criteria for Adverse Events) version 3.0. Despite the advanced stage of disease and frailty of our study population, there were no unexpected side effects. The most common AEs were hematologic. Neutropenia was observed in nine (40.9%) patients and of grade≥3 in six (27.2%). No febrile neutropenia occurred. The most common nonhematologic AEs were diarrhea and asthenia, reported in eight (36.3%) and in five (22.7%) patients, respectively. In this setting, Cbz toxicity seems to be manageable and comparable with second-line Cbz. Therefore, our results seem to support the safety of Cbz as a third-line treatment for mCRPC patients.